The local legend about Timur’s death in Otrar and modern studies - Yeldar Abdykalykov, Mukhtar Kozha, Ergali Satov, Almas Bektanov, Moldir Aldabergenova, (Opción, 2019)
The article is devoted to the study of local legends about the death of Timur and the analysis of archaeological materials. In the article, historical-comparative methods and the traditional characteristics of the study of linguistic data were used. Analyzing the results of archaeological excavations can be argued that the written sources in many ways objectively described the events that took place in the last days of Timur’s life. As a conclusion, the Otrar legend and data from sources of origin show that Timur spent the last days in the Otrar citadel, in the residence of Berdibek.